(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
The results of research of dynamic changes in a number of cortical zones activity at the students with different creativity parameters, during composing a story on the base of the presented words from different semantic fields are submitted. The intergroup difference in dynamic changes of level cortex activity in the examinees with different level of creative abilities was found out, that testifies the presence of various mechanisms of creative process maintenance.